THE EFFECT OF USING GENERATING INTERACTION SCHEMATA AND TEXT (GIST) STRATEGY TOWARD STUDENTS READING COMPERENSHION - Ernawati; Ade Sudirman; Riandi (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2023)
This research paper aims to determine The Effect of generating interaction schemata and text Strategy Towards Students’ Narrative Reading Comprehension Grade at the Tenth of SMAN 1 Cigemblong. This study used a quantitative approach with a quasi-experimental design research method, which uses three concepts, namely, pre-test, treatment and post-test. Which is where a pre-test would be carried out before giving treatment, and treatment carried out in five meetings, after giving treatment, students given a post-test to get the results of this study. The result reveal that using the strategy generating interaction schemata and text (GIST) is very helpful and easy for students to learn, this media can improve students' reading comprehension.